The effect of different surface treatments on repair of CAD/CAM hybrid ceramic with resin composite - Özlem Acar (Gazi University, 2016)
OBJECTIVE: The aim of this study was to evaluate the shear bond strength of novel hybrid ceramic material repaired with a composite resin. MATERIALS and METHOD: CAD/CAM hybrid ceramic (VITA Enamic) specimens were prepared. The bonding surface was abraded with 600, 800 and 1200 grit SiC papers, and treated with air abrasion of 50 µm alumina particles. The specimens were assigned to four groups (n=12). G1: etching with 34% phosphoric acid + bonding with Adper Single Bond 2, G2: etching with 8% hydrofluoric acid + silane application + bonding with Adper Single Bond 2, G3: etching with 34% phosphoric acid + bonding with Single Bond Universal, G4: etching with 8% hydrofluoric acid + silane application + bonding with Single Bond Universal. Composite resin was build up on pretreated specimens and light-polymerized. The specimens were thermocycled 1000 times between 5±2 °C and 55±2 °C. Shear bond strength test was done by using a universal testing machine at a 1 mm/min crosshead speed. Data were statistically analyzed with One Way ANOVA and post-hoc Tukey HSD tests. Results: Comparison of the shear bond strength among groups revealed statistically significant differences (p<0.05). No statistically significant difference was found between G1 and G3 (p=0.591). Statistically significant differences were found between G1 and G2 (p=0.024), and G1 and G4 (p=0.013). Adhesive failure was observed in all groups. Conclusion: Hydrofluoric acid etching reduced the composite resin to hybrid ceramic shear bond strength. Etching with phosphoric acid followed by bonding with Adper Single Bond 2 or Single Bond Universal positively influenced the bond strength of composite resin to hybrid ceramic.